ANALISIS INVESTASI PLTS SEBAGAI SUPLAI DAYA POMPA AIR TEMEGA PERUMDA TIRTA TOHLANGKIR KECAMATAN KARANGASEM - Ferdi Pratama, I Gede; Setiawan, I Nyoman; Sukerayasa, I Wayan (Jurnal SPEKTRUM; Vol 11 No 4 (2024): Jurnal SPEKTRUM, 2024)
Solar Power is a power generation tools modifier sunlight into electrical energy with various benefits for life. This research aims to analyze the investment of PLTS as a power supply for Temega water pump Perumda Tirta Tohlangkir, Karangasem District. In the investment analysis, this capstone project uses three indicators of investment feasibility in each scenario, including Net Present Value (NPV), Profitability Index (PI) also Payback Period (PP). A project stated to be worthy if the NPV value is more than 0 (>0), the PI value is more than 1 (>1), and the PP value is smaller than the project age (25 years). It can be concluded that the design of PLTS Temega Water Pump Perumda Tirta Tohlangkir Karangasem District scenarios 1, 2, and 3 are declared feasible to implement because they have met the three criteria for economic investment feasibility.